Implementasi Materi Fiqih Wanita Dalam Kegiatan Keputrian Untuk Meningkatkan Pemahaman Fiqih Siswi di MTs Thoriqul Huda Dimong Madiun - Ro’yun Niswati Ahada (Hikamatzu | Journal of Multidisciplinary, 2025)
Research on the implementation of the Activities of women in Fiqh Material Keputrian to improve the understanding of Fiqh. The purpose of this research is to know the process of the implementation of the activities of the keputrian, to know the increased understanding of Fiqh, and factor supporters and restricting the activities of keputrian in MTs Thoriqul Huda Madiun. This research was qualitative research with data collection techniques interviews, observation, and documentation. While the analysis technique used is the reduction of the data (data reduction), the presentation of data (data display), and conclusion (verification). From research conducted can be inferred that: The application of the maternal activities that have been carried out by female students in the field of women's jurisprudence for students is very much, especially in their understanding based on the experience they get from each activity and also every material given, all starting from the understanding that students will play and run according to syari’at. Like students who already know how to estimate the calculation of the right menstrual schedule along with their characteristics, morals in association with the opposite sex who are already getting used to not being too close, and how to dress that has started according to the shari'ah